A SEMANTIC ANALYSIS OF CONNOTATIVE MEANING IN BEN HOWARD’S SONG LYRICS - Chyntia Heru Woro Prastiwi; Meiga Ratih Tirtanawati; Fauziyah, Nina Irnisa (Aisyah Journal of English Language Teaching (AIJELT), 2024)
In linguistics, semantics studies how meaning is expressed through language, including sentences, phrases, and words. Connotative meaning, which gives words emotional depth and resonance, is significant in song lyrics. This study, titled “A Semantic Analysis of Connotative Meaning in Ben Howard’s Song Lyrics,” aims to explore the connotative meanings in Ben Howard's lyrics. The researcher chose five of his most popular songs on Spotify for this analysis. Using a qualitative descriptive analysis approach, the study looks into the sense of values and types of connotative meanings in the lyrics. The analysis shows that the songs’ themes affect the types of connotations found. Songs about love, vulnerability, and youth memories tend to have positive connotations, while themes of self-doubt, separation, and searching for life’s meaning have more negative and neutral connotations. Moreover, associative meaning is the most common connotative form, followed by affective, reflective, and allusive meanings. The findings indicate that song themes greatly influence the types of connotations used, with positive connotations more frequent in hopeful songs and negative ones in introspective songs. This research adds to language studies by offering insights into the complex and rich meanings in Ben Howard’s song lyrics.